Quality of antenatal care and its sociodemographic determinants: results of the 2015 Pelotas birth cohort, Brazil - Lina Sofia Morón-Duarte; Andrea Ramirez Varela; Andrea Dâmaso Bertoldi; Marlos R. Domingues; Fernando C. Wehrmeister; Mariangela Freitas Silveira (BMC, 2021)
Abstract Background Inadequate antenatal care (ANC) has been associated with adverse pregnancy outcomes. ANC quality is considered a key component of the right to health and a route to equity and dignity for women and their children. Although ANC coverage is relatively high in Brazil, there are revealed some health disparities when coverage is examined by socio-demographic determinants. In this study we evaluated ANC quality and its socio-demographic determinants using data from the 2015 Pelotas birth cohort, Rio Grande do Sul, Brazil. Methods This study is part of the 2015 Pelotas population-based birth cohort (n = 3923 pregnant women) conducted in southern Brazil. ANC quality was assessed through 19 content and service utilization indicators recommended by the Brazilian Ministry of Health. Descriptive analyses and associations of each of the ANC indicators and independent variables were performed using the chi-square and linear trend test. ANC indicators were analyzed individually and aggregated as a score. Associations between ANC score quality and socio-demographic variables were assessed with ordinal regressions. Mediation analysis with G-computation was performed to estimate direct and indirect effect of mother's level of education on ANC quality mediated by the number of consultations and timing of ANC initiation. Base and post confounders were included. Results The results showed that except for breast examination, height measurement, tetanus toxoid vaccination and ANC starting at the first trimester, all ANC indicators showed more than 80% coverage during ANC visits. In the adjusted analysis, inadequate quality ANC was associated with lower maternal education level, not having a partner, being multiparous, being attended by a private provider and by the same professional in all consultations. In the mediation analyses, 6.8% of the association between ANC quality and mother's education was mediated by the trimester in which ANC started, while 12.8% was mediated by the number of ANC visits. Conclusions ANC quality is associated with pregnant women's socio-demographic characteristics. Significant efforts are needed to improve the quality of facility-based maternity care.